FRAMING AS LEGITIMATION OF CLIMATE POLICY. CLIMATE CHANGE FRAMES IN ARGENTINIAN AND BRAZILIAN PRESS DURING THE SUMMITS OF DOHA AND WARSAW - Luis González Alcaraz (Disertaciones, 2014)
The article aims to describe and compare journalistic frames of climate change produced by two leading newspapers in South America: Clarin of Argentina and Folha de São Paulo of Brazil, in the context of the Doha (COP- 18) and Warsaw (COP -19) conferences. For this, it has used a definition of framing which recognizes its various dimensions: definition of the situation, reasoning about causes, moral evaluations and recommendations or prescriptions. The analysis was addressed by a qualitative process of coding and classification of journalistic texts. The empirical results indicate that the frames produced for the newspapers correspond to the political context to which they belong, that they coincide in pointing to climate change as a serious problem caused primarily by industrialized countries and what must be faced with a sense of urgency, so they tend to legitimate climate policy. In this regard, it is noted that journalistic frames not only guide the interpretation of social problems, but legitimate political action.